Return Saham Perusahaan Pertambangan pada Masa Pandemi Covid-19 di Indonesia - Lisandri Lisandri; Soelistijono Boedi; Akhmad Yafiz Syam; Steven Aditiajaya; Suriansyah Suriansyah (Owner : Riset dan Jurnal Akuntansi, 2023)
This research is a quantitative research. This study aims to test and analyze empirically the effect of Profitability, Leverage, Liquidity, and Company Size on stock returns. This study uses secondary data with a sample of 47 insurance sub-sector companies listed on the Indonesia Stock Exchange in 2019-2021 which were obtained using a purposive sampling method. Data analysis in this study used a multiple linear regression model. The results of this study indicate that Profitability, Leverage, Liquidity have no effect on stock returns. Meanwhile, company size has an effect on stock returns. The economic situation during the pandemic had an impact on obtaining stock returns so that investors tended to pay attention to firm size when investing. It is recommended that future research to focus on post pandemic periods so that the results may differ from this study.